(untitled) (The Research of Medical Science Review, 2025)
Background: Cervical cancer is the third leading cause of death among women globally, with human papillomavirus (HPV) identified as a major risk factor. Objectives: This study aimed to assess the knowledge and attitudes of women in Lahore, Pakistan, regarding cervical cancer prevention. Materials and Methods: A descriptive, hospital-based cross-sectional study was conducted in Lahore from September to December 2023. Data were collected using a structured questionnaire and analyzed through descriptive statistics, including frequencies, means, and percentages. Results: The study included 100 women, with a mean age of 18 ± 30 years. Awareness of cervical cancer and the Pap test was reported by 81% and 32% of participants, respectively. Most respondents associated cervical cancer with smoking (70.2%), multiple sexual partners (80.8%), and high parity (63.1%). Additionally, prolonged contraceptive use (62.6%), HPV infection (80.9%), and smoking (76.6%) were recognized as key risk factors. Only 35.4% correctly identified the appropriate timing for HPV vaccination as before marriage. Regression analysis indicated that marital status, education, occupation, and family income significantly influenced knowledge and attitudes. Conclusion: Participants’ knowledge and attitudes were shaped by socio-demographic factors. The study underscores the urgent need for national-level health education campaigns, including social media outreach, to raise awareness about cervical cancer prevention and control.